The Interface Interaction of C3N4/Bi2S3 Promoted the Separation of Excitons and the Extraction of Free Photogenerated Carriers in the Broadband Light Spectrum Range - Xingfa Ma; Xintao Zhang; Mingjun Gao; Ruifen Hu; You Wang; Guang Li (Inorganics)
Exciton generation and separation play an important role in the photoelectric properties and the luminescence performance of materials. In order to tailor the defects and grain boundaries and improve the exciton separation and light harvesting of the graphitic carbon nitride (g-C3N4) nanosheets, a C3N4/bismuth sulfide (Bi2S3) nanocomposite was synthesized. The photoelectric properties of the 405, 532, 650, 780, 808, 980 and 1064 nm light sources were studied using Au electrodes and graphite electrodes with 4B and 5B pencil drawings. The results indicate that the C3N4/Bi2S3 nanocomposite exhibited photocurrent switching behavior in the broadband light spectrum range. It is noted that even with zero bias applied, a good photoelectric signal was still measured. The resulting nanocomposite exhibited good photophysical stability. Physical mechanisms are discussed herein. It is suggested that the interfacial interaction of C3N4 and Bi2S3 in the nanocomposite creates a strong built-in electric field, which accelerates the separation of excitons. Therefore, as a dynamic process of photoexcitation, fluorescence, the photoelectric effect, and scattering are three main competing processes; the separation of excitons and the extraction of free photogenerated charge can be used as a reference for the fluorescent materials or other photoelectric materials studies as photophysical properties. This study also serves as an important reference for the design, defect and grain boundary modulation or interdisciplinary application of functional nanocomposites, especially for the bandgap modulation and suppression of photogenerated carrier recombination.